Revisit the Sedimentary Stratigraphic Evolution and Environmental Changes on the Outer Shelf of the East China Sea Since MIS 5 - Wang, Zhongbo; Yang, Shouye; Tang, Haiyan; Zheng, Yilin; Wang, Hongyue; Zhang, Zhixun; Zhang, Yong; Mei, Xi; Wang, Qiang; Lai, Zhongping (Frontiers in Marine Science, 2022)
The East China Sea (ECS) is featured by the broad continental shelf, huge terrigenous sediment input and striking river-sea interaction during the Quaternary. Despite the numerous studies, mostly on the delta, coastal and inner shelf areas, the late Quaternary stratigraphy and sedimentary environment on the mid-outer ECS shelf were poorly documented. In particular, it is still controversial in issues such as the recognition of marine transgression deposits in the interglacial period and the occurrence and ages of deposits in the glacial period. This study presents new data of high-resolution seismic reflection profiles and collective evidences from lithology, microfossil assemblages and geochronology of borehole SFK-1 on the ECS outer shelf, aiming to revisit the sedimentary stratigraphic evolution and environmental changes since the Marine Isotopic Stage 5 (MIS 5). Sixty-one ages were obtained by radiocarbon and Optical Stimulation Luminescence (OSL), providing robust constraints on the chronostratigraphy. Three marine regression/transgression cycles were identified, which primarily constrained the sedimentary environmental evolution over the past 100 kyrs. Although the strong river-sea interaction accompanied with sea level fluctuations characterized the late Quaternary depositional environment on the shelf, this study clearly identified the stratigraphic boundaries between MIS 1 and MIS 5, and confirmed the tide-influenced fluvial deposition formed during the Last Glacial Maximum on the outer shelf. We infer that tidal forcing significantly superimposed its influence on sea level change and thus formed the most striking feature on the late Quaternary stratigraphy of the open ECS shelf. With the combination of a large number of absolute depositional ages with high-resolution core records, the major findings of this study may allow better understanding of the Quaternary sedimentary evolution and river-sea interaction on open shelves dominated by siliciclastic sedimentation.